2016
DOI: 10.1002/ldr.2531
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Connectivity Does Change Over 70 Years of Abandonment and Afforestation in the Spanish Pyrenees

Abstract: Runoff connectivity depends on topography, rainfall, man-made elements (terraces, trails, roads and drainage systems) and vegetation. In this study, we quantified the effects of 70 years of human activities on runoff connectivity in the mountainous Araguás afforested sub-catchment (17·2 ha; Central Spanish Pyrenees). The IC index of hydrological connectivity was chosen to perform this metric over six land use scenarios at high spatial resolution (1 × 1 m of cell size). The current scenario (year 2012) was simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 43 publications
(83 reference statements)
0
40
0
1
Order By: Relevance
“…Runoff connectivity (López‐Vicente, Nadal‐Romero, & Cammeraat, ; Zimmermann, Zimmermann, Turner, Francke, & Elsenbeer, ) possibly explains the large changes in sediment source contributions observed over very short distances between sampling site, that is, the coarse sediment being able to pass from the eucalyptus stand through the areas of riparian forest to the river, but fine sediment was not, and in some sites, sediment being able to move from the road through the eucalyptus stand to the river without any sediment being contributed from the eucalyptus stand at the same time. Zimmermann et al () found that seasonal differences in moisture strongly influence connectivity, even under light rainfall conditions but are increased rapidly as rainfall frequency raises, eventually leading to full connectivity and surface drainage of entire hillslopes.…”
Section: Discussionmentioning
confidence: 99%
“…Runoff connectivity (López‐Vicente, Nadal‐Romero, & Cammeraat, ; Zimmermann, Zimmermann, Turner, Francke, & Elsenbeer, ) possibly explains the large changes in sediment source contributions observed over very short distances between sampling site, that is, the coarse sediment being able to pass from the eucalyptus stand through the areas of riparian forest to the river, but fine sediment was not, and in some sites, sediment being able to move from the road through the eucalyptus stand to the river without any sediment being contributed from the eucalyptus stand at the same time. Zimmermann et al () found that seasonal differences in moisture strongly influence connectivity, even under light rainfall conditions but are increased rapidly as rainfall frequency raises, eventually leading to full connectivity and surface drainage of entire hillslopes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this index takes into account all the links between a cell and all other components of the catchment, in agreement with the definition of connectivity. Third, the index can be mapped enabling comparisons between various locations (a specific tool has been developed in ArcGIS), and the calculation of maps of connectivity evolution over time (see, for example, case study applications in, among others, Foerster at al., 2014 andLópez-Vicente et al, 2016). Nevertheless, this index remains empirical and comparisons between catchments should be made carefully.…”
Section: State Of the Artmentioning
confidence: 99%
“…The ability of this index has been proved in different fields and catchments, such as in Austria (Heckmann & Schwanghart, ), France (Gay et al, ) and Japan (Chartin et al, ). In Spain, the studies of López‐Vicente et al (, ) and Foerster et al () proved their capacity to map runoff and sediment connectivity.…”
Section: Introductionmentioning
confidence: 99%